RUMAH PERLINDUNGAN BAGI PEREMPUAN DI BANJARBARU - Bayurini, Nayla Aswinda; Tharziansyah, Muhammad; Dahliani, Dahliani (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
Based on data from the online information system for the protection of women and children (SIMFONI-PPA) in 2023, the number of cases of violence against women in Indonesia reached 26,161 victims and in the province of South Kalimantan there were 531 cases with the number of cases in Banjarbaru City being 61 cases. Violence against women and children is widely heard in society today and is a very common occurrence in a home. This makes a home no longer a safe place for women and children and ultimately seeks a safe place for them to live temporarily. However, the DPPPA of South Kalimantan Province, which is a place for complaints, does not yet have a permanent shelter for victims who make complaints. So that a shelter is needed for women in the province of South Kalimantan. Therefore, there needs to be a Women's Shelter in Banjarbaru by prioritizing the physical and psychological security aspects of users. This is realized by the Spatial Psychology method with the Triple Shield concept which is combined with Safe, Secure, & Serenity to create a Safe House for women physically and psychologically.